THE RELATIONSHIP BETWEEN THE APACHE II SCORE AND THE NUMBER OF DAYS OF HOSPITALIZATION IN THE INTENSIVE CARE UNIT (ICU) AT HARAPAN INSAN HOSPITAL, SENDAWAR WEST KUTAI - Lydia Lydia; A.Lis Arming; Setiani Setiani (Cerdika: Jurnal Ilmiah Indonesia, 2023)
The APACHE II score is a method for determining disease severity and assessing patient mortality in ICU. The result of measuring the patient's condition was obtained in the first 24 hours of admission to the ICU. Scoring is used to estimate prognostic risk factors for patients who can leave the ICU room in recovering or dying conditions. The length of hospitalization for patients in the Intensive Care Unit (ICU) is on average more than 5 days. The purpose of this study was to determine the relationship between the APACHE II score and the range of days in the Intensive Care Unit (ICU) at RSUD Harapan Insan Sendawar West Kutai. The design of this study was cross-sectional. The sampling technique in this study used accidental sampling, and the research samplers were 30 respondents. The test instrument used the APACHE II Observation sheet. The results of the statistical analysis of the bivariate test using Chi-Square obtained a p-value of 0.757, which is greater than the alpha value, it means that there is no relationship between the APACHE II score and the range of days of hospitalization in the Intensive Care Unit (ICU) at Harapan Insan Hospital, Sendawar, West Kutai. The Odds Ratio (OR) value was obtained at 0.786, which means that patients who have an APACHE II score were in a low category, and they have an opportunity of 0.786 times to have a range of days of hospitalization in the category of short hospital days. There is no relationship between the APACHE II score and the range of days of hospitalization in the Intensive Care Unit (ICU) at Harapan Insan Hospital, Sendawar, West Kutai. The suggestions for hospital management to add beds in the ICU and the results of the research are expected to be guidelines for patient care in the ICU by using the APACHE II score and improving services in the ICU